Concepts Employee Productivity, Analysis in the Ground Handling Sector: A Literature Review Study - Muhammad Tohir; Andri Primadi; Lira Agusinta; Euis Saribanon; Danang Darunanto; Primadi Candra Susanto (Goodwood Publishing, 2026)
Purpose: This study aimed to identify factors that influence employee productivity in Indonesia’s ground handling sector. The research approach used is a literature review, which synthesizes findings from various previous international, indexed scientific articles relevant to the research topic. Methodology: This study used a descriptive qualitative research method with a literature review approach. Data were collected from reputable, internationally indexed articles obtained from Scopus, Web of Science, Emerald, Springer, and Google Scholar databases. The selected literature was analyzed using reduction techniques, data presentation in matrix form, and comparative synthesis to identify patterns, similarities, and differences between studies. Results: The results show that organizational culture, organizational commitment, and remuneration affect the work productivity of ground handling sector employees directly or indirectly through job satisfaction. Conclusions: This study concludes that organizational culture, commitment, and remuneration influence employee productivity in the ground handling sector, both directly and indirectly through job satisfaction. Therefore, improving job satisfaction is essential for strengthening work quality, quantity, and punctuality. Limitations: This study’s limitation is that it relies solely on the synthesis of various scientific articles and does not involve field data from ground handling companies directly. This limits the study's ability to capture the actual operational conditions, technical challenges, and human resource dynamics on the apron or terminal. Contributions: Given the limited research on Human Resource Management (HRM) in the ground handling sector, this study contributes to the development of the literature in this highly technical and high-risk sector.